Unraveling the impact of social dynamism on student stress amidst COVID-19 - Md Nazrul, Islam; Abdul Rahman, Haliza (IGI Global, 2023)
The COVID-19 pandemic has significantly impacted school students, causing heightened levels of stress and reshaping social dynamics within educational settings. This study aims to unravel the complex relationship between COVID-19-related stress and social dynamics among school students. By exploring factors such as changes in peer interactions, alterations in classroom environments, the impact of remote learning and limited social contact, as well as disparities in access to technology and internet connectivity, this research seeks to understand the far-reaching consequences of the pandemic on students' well-being. Additionally, this study examines the application of social systems, social support theory, and the transactional model of stress and coping in the context of the COVID-19 pandemic. The findings from this research contribute to a deeper understanding of the interplay between social dynamics and COVID-19-related stress among school students, with implications for developing effective interventions and support systems.